(3GdLhGfH GdJUejejI dMOGFb GdefefeGJ (B: s (3OQGSI GdMGdI GdeUQjI (B/ s - (3fgi CMeO eMeO GdfGOis; (3CMeO eMeO Cejf (B: s; (3YdjGA MSjf GdSGOGJi (B: s ((3GdbGgQI (B: s (3fgi CMeO eMeO GdfGOi (B: s, 2019)
(3jgOa GdHMK Edi GdGSJaGOI ef GdJLGQH GdYGdejI dMOGFb GdoefefeGJ dGSJNdGU (B{u(3200F(B}(3GdeYGjjQ GdeNJdaI dHfGA h EOGQI MOGFb oefefeGJ fGLMI hLnqPGHI(B: (3h Pdc ef NdGd GdOQGSI GdfXQjI (B{u(3200F(B}(3GdJi JTed OQGSI JGQjN JWhQ MOGFb GdoefefeGJ h JUfjaGJgG(B: (3h GdYfGUQ GdJUejejI h GdCHYGO (B{u(3200F(B}(3GdJbfjI GdJi jLH eQGYGJgG YfO GdJUeje(B. (3ef NdGd eLehYI ef GdMOGFb GdYGdejI(B: (3Je (B{u(3200F(B}(3GSJNdGU YOkOG ef GdCSS h GdeYGjjQ GdJUejejI(B: (3h GSJNOGegG ai bjGS caGAg MOGFb (B{u(3200F(B}(3GdoefefeGJ GdeUQjI(B. (3JfJgi GdOQGSI HYOO ef GdJhUjGJ dJMhjd MOGFb GdefefeGJ GdeUQjI Edi (B{u(3200F(B}(3MOGFb PGJ bOQI JfGaSjI Ydi GdeSJhi GdYGdei(B: (3JYed HcaGAI h aGYdjI dJfejI hJMajR GdeLJeY (B{u(3200F(B}(3GdeMdi GdeMjW HgGs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdEOGQIs; (3GdJUejes; (3MOGFb GdefefeGJs